MANAJEMEN KESISWAAN DAN MANAJEMEN KEUANGAN DI SMA - Mursilah Mursilah (UNIVERSITAS BENGKULU, 2015)
The purpose of this study is to describe the student anagement and financial management at SMAN 2 South Bengkulu . This research is a qualitative descriptive study. Subjects were principals, teachers, staff education personnel. Data collection techniques through: observation, interviews , and documentation . Conclusion The results of the study are : ( 1 ) the field of management of the school the student has at least three major tasks , namely the admission of new students , the learning progress of activities , and mentoring and coaching discipline ; ( 2 ) The main components of the financial management of the school include: budgetary procedures , financial accounting , learning , warehousing , distribution , investment , and inspection .Keywords : management , student affairs , finance